Revision of the shell-carrying crab genus Conchoecetes Stimpson, 1858 (Crustacea: Brachyura: Dromiidae) - Mclay, Colin L.; Naruse, Tohru (Zootaxa, 2019)
The genus Conchoecetes Stimpson, 1858, has long been considered to include three species: C. artificiosus (Fabricius, 1798), C. andamanicus Alcock, 1900, and C. intermedius Lewinsohn, 1984. The type species, C. artificiosus, has been assumed to be widely distributed throughout the Indo-West Pacific and a fourth species, C. conchifera (Haswell, 1882), from Australia, has been regarded as a synonym. The enigmatic and long overlooked “Caphyra pectenicola Adams, in Belcher, 1848” is shown to be a species of Conchoecetes occurring in Java, Singapore and the Gulf of Thailand. We review the status of these species, establish C. conchifera as a valid species, and describe five new species: C. atlas n. sp., C avikele n. sp., C. chanty n. sp., C. investigator n. sp. and C. pembawa n. sp. In this revision we recognize 10 valid species in Conchoecetes. They are distributed from Southern Africa, across the Indian Ocean to Australia and northwards to China. Formerly considered to be cosmopolitan, C. artificiosus is restricted to India, Sri Lanka Pakistan, as well as the Persian Gulf and Madagascar, while C. intermedius, first discovered near Madagascar, is shown to be the most widespread species occurring from Africa to China.